1990
DOI: 10.1093/oxfordjournals.eurheartj.a059802
|View full text |Cite
|
Sign up to set email alerts
|

Exercise-induced platelet aggregation in angina and its possible prevention by β1-selective blockade

Abstract: Moderate exercise increased platelet aggregability of 12 middle-aged men with stable angina pectoris: the mean ADP threshold fell from 4.58 +/- 0.63 to 3.18 +/- 0.41 microM, P less than 0.01. Exercise did not, however, alter platelet aggregability in 12 healthy matched controls. Physical effort approximately doubled the plasma levels of adrenaline and noradrenaline in patients as well as in controls. Under the same conditions the cAMP content of platelets fell in the angina group from 20.86 +/- 1.86 to 17.78 +… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

1992
1992
2006
2006

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 0 publications
1
7
0
Order By: Relevance
“…Indeed, despite the enhanced platelet reactivity at baseline, patients with NCAs exhibited a significant reduction in platelet reactivity after exercise, whereas CAD patients, in agreement with previous studies, [1][2][3][4][5] showed a significant increase.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Indeed, despite the enhanced platelet reactivity at baseline, patients with NCAs exhibited a significant reduction in platelet reactivity after exercise, whereas CAD patients, in agreement with previous studies, [1][2][3][4][5] showed a significant increase.…”
Section: Discussionsupporting
confidence: 90%
“…A careful clinical history, including risk factors for CAD and drug therapy, was recorded from each patient. Patients with any of the following conditions were excluded: (1) myocardial infarction or unstable angina in the previous 6 months; (2) anticoagulant therapy; (3) previous coronary angiography; (4) previous revascularization procedures (surgical or percutaneous); and (5) variant angina.…”
Section: Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies of moderate or sub-maximal exercise yielded conflicting results varying from suppressed platelet function through to elevated activity [14,16,17]. In CAD, there is evidence to suggest an association between exercise and increased platelet activity although the relationship between exercise intensity and platelet activation is not well defined [18][19][20][21]. However, other work has shown that exercise has no effect on platelet function [22], and at least one study suggests a reduction in platelet activity in CAD patients with exercise [23].…”
Section: Discussionmentioning
confidence: 99%
“…The 1 -selective blocker MET, in usual therapeutic dosages, prevented the observed platelet changes in exerciseinduced platelet aggregation in angina probably by minimising the haemodynamic disturbances and stimulating release of prostacyclin [87]. However, MET prevented the increase of platelet aggregability and the decrease of intracellular cAMP during exercise stress in patients with stable angina pectoris [88].…”
Section: Bab Drugs -Effect On Aggregation and Coagulation; Volunteersmentioning
confidence: 99%